Novel LCK/FMS inhibitors based on phenoxypyrimidine scaffold as potential treatment for inflammatory disorders - Farag, Ahmed Karam; Elkamhawy, Ahmed; Londhe, Ashwini M.; Lee, Kyung-Tae; Pae, Ae Nim; Roh, Eun Joo (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2017)
Tyrosine kinases including LCK and FMS are involved in inflammatory disorders as well as many types of cancer. Our team has designed and synthesized thirty novel pyrimidine based inhibitors targeting LCK, classified into four different series (amides, ureas, imines (Schiff base) and benzylamines). Twelve of them showed nanomolar 1050 values. Compound 7g showed excellent selectivity profile and was selectively potent over FMS kinase (1050 value of 4.6 nM). Molecular docking study was performed to help us rationalize the obtained results and predict the possible binding mode for our compounds in both LCK and FMS. Based on the obtained biological assay data and modelling results, a detailed SAR study was discussed. As a further testing regarding the anti-inflammatory effect of the new compounds, in vitro cellular assay over RAW 264.7 macrophages was performed. Compound 7g exhibited excellent antiinflammatory effect. Therefore, we report the design of novel phenoxypyrimidine derivatives as potent and selective LCK inhibitors and the discovery of 7g as potent and selective FMS/LCK dual inhibitor for the potential application in inflammatory disorders including rheumatoid arthritis (RA). (C) 2017 Published by Elsevier Masson SAS.
Keywords: VIVO ANTIINFLAMMATORY ACTIVITY; LYMPHOCYTE-SPECIFIC KINASE; SRC-FAMILY KINASES; COLONY-STIMULATING FACTORS; ORGAN ALLOGRAFT-REJECTION; ORALLY-ACTIVE INHIBITORS; ACUTE MYELOID-LEUKEMIA; IN-VIVO; SIGNAL-TRANSDUCTION; TYROSINE KINASE